2015
DOI: 10.1089/ten.tea.2014.0327
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Stromal Cells on the Pigmentation of Tissue-Engineered Dermo-Epidermal Skin Grafts

Abstract: It has been shown in vitro that melanocyte proliferation and function in palmoplantar skin is regulated by mesenchymal factors derived from fibroblasts. In this study, we investigated in vivo the influence of mesenchymal-epithelial interactions in human tissue-engineered skin substitutes reconstructed from palmarand nonpalmoplantar-derived fibroblasts. Tissue-engineered dermo-epidermal analogs based on collagen type I hydrogels were populated with either human palmar or nonpalmoplantar fibroblasts and seeded w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Moreover, the original color of the donor skin was restored after transplantation (Biedermann et al 2015b;Böttcher-Haberzeth et al 2013). Distinct MelSkin substitutes differing in color (light or dark) showed physiological melanocyte distribution and function even 15 weeks after transplantation (Biedermann et al 2015a;Böttcher-Haberzeth et al 2014). We show here that MelSkin can adapt its melanin content as a reaction to UVB exposure, namely by an increased production of melanin and its transfer to the upper layers of epidermal keratinocytes.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, the original color of the donor skin was restored after transplantation (Biedermann et al 2015b;Böttcher-Haberzeth et al 2013). Distinct MelSkin substitutes differing in color (light or dark) showed physiological melanocyte distribution and function even 15 weeks after transplantation (Biedermann et al 2015a;Böttcher-Haberzeth et al 2014). We show here that MelSkin can adapt its melanin content as a reaction to UVB exposure, namely by an increased production of melanin and its transfer to the upper layers of epidermal keratinocytes.…”
Section: Discussionmentioning
confidence: 69%
“…This was of particular interest because ASCs represent an abundant cell source and can be used as a substitute for dermal Fbs, especially if the latter are limited in number. To gain more insight into this matter, we bioengineered pigmented dermo-epidermal skin substitutes (melDESS) containing epidermal melanocytes and keratinocytes and differing in the distinct types of stromal cells in the dermal part (Biedermann et al, 2015b). The overall results showed an anti-melanogenic effect of ASCs.…”
Section: Discussionmentioning
confidence: 99%
“…Previously we showed that the composition and properties of a particular stroma also varies significantly with respect to its body site (Biedermann et al, 2015b). As a consequence, we need to consider both from which dermal layer the stromal cells are derived and from which area of the body stromal cells are isolated to bioengineer a skin graft that optimally matches the color of the particular skin region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin pigmentation is regulated by crosstalk between melanocytes and adjacent skin cells such as epidermal keratinocytes and dermal fibroblasts (Yamaguchi and Hearing, 2009). Variation of skin color among different body sites is incompletely understood, although increasing evidence shows that mesenchymal cells, especially dermal fibroblasts, might play important roles through a paracrine mechanism (Biedermann et al, 2015;Cario-André et al, 2006;Choi et al, 2010;Yamaguchi et al, 2004). It is less certain if other skin mesenchymal cells such adipocytes or endothelial cells, which are normally not in direct contact with epidermal melanocytes, might influence pigmentation in certain clinically relevant circumstances, such as in engineered skin reconstructs.…”
mentioning
confidence: 99%